(3JaSjQ GdOfjhQis - (3CHh eMeO YHO Gddg Hf eMeO Hf hgH GdOjfhQj,J (B308 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ ShQI GdaGJMI s
(3BNQgG (B:s
(3jfJgi HJaSjQ Ghd ShQI Gdadb s
(3GdejcQhajde Hg Jda HSjWs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs